2018
DOI: 10.1016/j.foodhyd.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Release kinetics and antimicrobial properties of carvacrol encapsulated in electrospun poly-(ε-caprolactone) nanofibres. Application in starch multilayer films

Abstract: Release kinetics and antimicrobial properties of carvacrol encapsulated in electrospun poly-(ε-caprolactone) nanofibres. Application in starch multilayer films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 36 publications
6
39
0
Order By: Relevance
“…The inclusion of CA in a carrier polymeric matrix could be a useful way to deliver its effects (Turek and Stintzing 2013). In this sense, previous studies reported very slow-release kinetics of these kinds of compounds from PLA films (Muller et al 2017b), whereas their encapsulation in more hydrophilic polymers (zein, chitosan, cassava, and corn starch) favours the release, providing greater effectiveness as antimicrobial agents (Fabra et al 2016;Muller et al 2017b;Tampau et al 2018).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The inclusion of CA in a carrier polymeric matrix could be a useful way to deliver its effects (Turek and Stintzing 2013). In this sense, previous studies reported very slow-release kinetics of these kinds of compounds from PLA films (Muller et al 2017b), whereas their encapsulation in more hydrophilic polymers (zein, chitosan, cassava, and corn starch) favours the release, providing greater effectiveness as antimicrobial agents (Fabra et al 2016;Muller et al 2017b;Tampau et al 2018).…”
Section: Introductionmentioning
confidence: 92%
“…The incorporation of the active compound in the polymer matrix modified the barrier and Fig. 1 Mechanism of aminolisation by 1,6-hexanediamine, occurring at the polylactide's surface mechanical properties of the film to a different extent, as reported by Requena et al (2018) and Tampau et al (2018) when carvacrol was incorporated into starch-polyester-blend bilayers and starch-PCL-starch multilayers, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…The release of 1‐MCP was more abrupt at 60% to 90% RH. Tampau et al found that the release of antimicrobial carvacrol could be improved if it was encapsulated in electrospun poly‐(ε‐caprolactone) nanofibers. Using the electrospun nanofibers, the water permeability could be reduced in the multilayer system and control the release of the antimicrobial carvacrol.…”
Section: Resultsmentioning
confidence: 99%
“…15 wt.% PLA solutions (with or without 20 wt.% CA with respect to the polymer) were prepared by placing the PLA pellets in the selected solvent systems in hermetically sealed recipients and maintaining under magnetic stirring at room temperature (25 ± 1 °C) for 24 hr to ensure complete dissolution. The ratio CA–polymer was chosen on the basis of previous studies (Tampau, González‐Martínez, & Chiralt, 2018) to ensure enough load of CA in the matrix to exert its antimicrobial action when applied in the packaging films. Initially, EtAc was used in order to meet the requirements for food contact use.…”
Section: Methodsmentioning
confidence: 99%